TINJAUAN YURIDIS TERBENTUKNYA KERJASAMA KEIMIGRASIAN OLEH DIREKTORAT JENDERAL IMIGRASI: DASAR HUKUM DAN PERANANNYA - Hana Farah Dhiba; I Gusti Putu Anom Kresna Wardhana; Shafa Salsabila (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The Directorate General of Immigration as one of the government agencies under the Ministry of Law and Human Rights always carries out national and international cooperation, which falls within the scope of Immigration authority not only on the interests of Indonesian citizens but also related to foreign nationals. Cooperation in the field of immigration between the two parties certainly needs to have a strong legal basis in the manufacturing process and the resulting cooperation products. The formulation of the problem examined in this paper is what are the legal bases used in making immigration cooperation agreements by the Directorate General of Immigration with other agencies and how is the purpose of the legal basis in realizing the objectives of immigration cooperation. The research method used is descriptive-qualitative research and a normative juridical approach. From the research, it is known that the Directorate General of Immigration in implementing immigration cooperation has been based on various statutory regulations containing Indonesian immigration cooperation